THE WALL CRANEAND HIS MECHANISMS (Perner's Contacts, 2017)
This entry describe constructional design of a model wall crane. A crane trolley of the wall crane, in design as drawing crane is equipped trolley by lifting device, is situation of a jib of the model wall crane.
Keywords: crane trolley; crane travel; lifting device; wall crane